2006
DOI: 10.4314/jasem.v9i3.17364
|View full text |Cite
|
Sign up to set email alerts
|

The antisickling effects of dried fish (tilapia) And dried prawn (<i>Astacus red</i>)

Abstract: ABSTRACT:The antisickling effect of dried fish (Tilapia) and dried prawn (Astacus red) were investigated to ascertain the ability of the extracts of these samples to inhibit polymerisation of sickle cell haemoglobin (HbS), improve the Fe 2+ /Fe 3+ ratio and lower the activity of lactate dehydrogenase (LDH) in blood plasma. The samples were first ground into powder and soaked in chloroform/dichloromethane to defat them and in essence produce the fat soluble fraction (filtrate). The defatted residues were soaked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In contrast, it has also been found that most antisickling agents eg. Amino acids, sugars, vitamins and peptides are devoid of toxicity (Ekeke and Shode, 1990;Ekeke et al, 2000Ekeke et al, , 2001Nwaoguikpe and Uwakwe, 2005;Uwakwe and Nwaoguikpe, 2008) .The antisickling effects of the nutrients mentioned above are based on the following mechanisms. It has been elucidated that amino acids , peptides and sugars raise the minimum gelling concentration of HbSS such that the protein does not polymerize at physiological conditions (Diego and Jen, 1977;Dean and Schechter, 1978).These antisickling agents also inhibit sickling by binding at the hemepocket obstructing the protein-protein interaction required for fiber formation in gelation (Noguchi and Schechter, 1978;Diego and Jen, 1977 ;Efenwonkiekie et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it has also been found that most antisickling agents eg. Amino acids, sugars, vitamins and peptides are devoid of toxicity (Ekeke and Shode, 1990;Ekeke et al, 2000Ekeke et al, , 2001Nwaoguikpe and Uwakwe, 2005;Uwakwe and Nwaoguikpe, 2008) .The antisickling effects of the nutrients mentioned above are based on the following mechanisms. It has been elucidated that amino acids , peptides and sugars raise the minimum gelling concentration of HbSS such that the protein does not polymerize at physiological conditions (Diego and Jen, 1977;Dean and Schechter, 1978).These antisickling agents also inhibit sickling by binding at the hemepocket obstructing the protein-protein interaction required for fiber formation in gelation (Noguchi and Schechter, 1978;Diego and Jen, 1977 ;Efenwonkiekie et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The antisickling effect of these samples is similar to that of Cajanus cajan , a leguminous seed having pronounced antisickling effectiveness. The extracts of this leguminous specie stabilizes the erythrocyte membrabe , improve the oxidant status of HbSS erythrocytes and lowers the activity of LDH in both serum and plasma of sickle cell blood (Ekeke and Shode, 1990;Nwaoguikpe, 1999;Nwaoguikpe and Uwakwe, 2005). These extracts may present a double-prong effect in the management of sickle cell disease and other related syndromes such as anemia and thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-sickling effects of various substances and the role of nutrition in overcoming SCD have been reported [8-10], although information on the management of SCD is still scarce. The antioxidant capability of Solenostemon monostachyus , Ipomoea involucrata , and Carica papaya seed oil has recently been reported [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…The results from this study using the reversal and inhibitory antisickling model however gave much higher antisickling activities at lower concentration and indicated that the ethanol extract of TO can be used as prophylactic drug in offsetting sickling crisis as well as be administered during crisis to reduce vaso occlusion and hence pain. Amino acids, iron as well as the vitamin C, had been implicated for antisickling activities,31, 32 and these together with the antioxidant contents of TO might be responsible for the high antisickling property (see Plate 1, Plate 2, Plate 3, Plate 4).
Plate 1Photomicrograph of sample blood film of an HbSS patient in steady state.
Plate 2Photomicrograph of sickled cells (95.0 %) in an HbSS blood sample following 1 h deoxygenation with nitrogen gas (Negative control).
Plate 3Photomicrograph of reversed HbSS red blood cells after treatment with T. occidentalis at 4 mg/mL.
Plate 4Photomicrograph of the inhibition of sickling of HbSS red blood cells by T. occidentalis at 4 mg/ml.
…”
Section: Resultsmentioning
confidence: 99%